The effectiveness of formulation of Lantana camara-based insecticides on looper caterpillar (Hyposidra talaca, Ectropis bhurmitra, Biston suppressaria) on tea plant - Dini Jamia Rayati (Jurnal Penelitian Teh dan Kina, 2011)
To obtain an environmentally sound control method of looper caterpillar (Hyposidra talaca, Ectropis bhurmitra, Biston suppressaria) as an alternative to reduce the use of chemical insecticide in tea estate, a study to evaluate the effect of the formulation of L. camara-based insecticide against looper caterpillar on tea plant has been conducted at Pasir Sarongge Experimental Garden (1,100 m asl), Cianjur, West Java. The trial was arranged in a randomized complete block design with six treatments, replicated four times. The treatments comprised: Formulation WP of L. camara-based insecticide with two doses, 1,5 kg/ha and 3,0 kg/ha; Formulation EC of L. camara-based insecticide with two doses, 1,5 l/ha and 3,0 l/ha; Standard chemical insecticide, Decis 25 EC (deltaÂmetrin) at 300 m/ha; and control. The L. camara-based insecticide and chemical insecticide were sprayed three times with one week interval, one day after plucking. The intensity of looper caterpillar attack was measured every week after spraying at the time of plucking. Results showed that all of the L. camara-based insecticide formulation treatments were effective against tea-looper caterpillar. The effectiveness in reducing the intensity of looper caterpillar attack were not significantly different each others, and were comparable to the standard chemical insecticide. The effectiveness level were relatively high, with the average of 45,25%. Based on these results it could be concluded that both formulation of WP and EC of Â L. camara-based insecticide could be used for controlling tea-looper caterpillar at lower dose, i.e. 1,5 kg/ha and 1,5 l/ha for the formulation of WP and EC, respectively.